Forms of stimuli and their effects on idea generation in terms of creativity metrics and non-obviousness. Issue 3 (2nd July 2020) - Borgianni, Yuri; Maccioni, Lorenzo; Fiorineschi, Lorenzo; Rotini, Federico
ABSTRACT: Idea generation is acknowledged to benefit from intentionally administered stimuli or designers' processes that include the search for external sources of inspiration. Text-based and graphic forms of stimuli are the most leveraged in design literature, but it has not been yet demonstrated which form is most effective for boosting creativity. This is due to the fact that previous studies have employed many varying conditions which do not allow for comparisons to be made. The present paper presents an experiment in which three groups of 27 participants were asked to generate new ideas for new-borns' outfits. To perform the task, the participants first considered five stimuli presented to them in one of the forms depending on which group the participants had been assigned to, i.e. textual, pictorial or combined (juxtaposition of the two). The stimuli were intended to share the semantic content, thus limiting potential bias due to different meanings. The outcomes of the experiment were evaluated in terms of creativity and non-obviousness. The presence of a pictorial dimension resulted in a significant increase in terms of rarity and non-obviousness of ideas, but did not affect quality, originality or quantity. The limited overlap among ideas emerging from the three forms suggests the potential value of developing design tools for idea generation that mix multiple forms of stimuli.